(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
India and Uzbekistan have a long history of cultural relations and whereas more recently the strategic partnership has been further entrenched. This study surveys the trajectory, present standing, and prospect of relations between the two countries against the backdrop of geopolitical changes-in Central Asia. Uzbekistan is at the centre of an Indian pivot in support of other growing initiatives-such as the Connect Central Asia Policy and the International North-South Transportation Corridor (INSTC), being more significant in relation to regional connectivity, energy security, and counter-terrorism cooperation. The other areas of cooperation may include trade, defence, education, and digital technology. The authors point out that absence of direct access routes and geopolitical competition from China and Russia, as well as institutional limitations, continue to hinder these opportunities.Using a qualitative method of inquiry, research draws on academic literature, policy papers, and government reports to address strategic alignments and gaps. Cooperative opportunities in renewable energy, pharmaceuticals, and soft-power diplomacy are also considered. The paper ends with some concrete policy recommendations that can help both countries address regional challenges and build a strong and strategic partnership that benefits both and is based on shared regional goals.